What about Pain in Disorders of Consciousness? - Schnakers, C.; Chatelle, C.; Demertzi, A.; Majerus, S.; Laureys, S. (The AAPS journal, 2012)
The management and treatment of acute pain is very difficult in non-communicative patients with disorders of consciousness ( i.e. , vegetative state/unresponsive wakefulness syndrome (VS/UWS) and minimally conscious state), creating an ethical dilemma for caregivers and an emotional burden among both relatives and caregivers. In this review, we summarize recent findings about the neural substrates of nociception and pain in VS/UWS patients as well as recent behavioral assessment methods of nociception specifically designed for patients in altered states of consciousness. We will finally discuss implications for pain treatment in these patients.